Strategy of Child Service Development at Representative Office Library Bank Of Indonesia North Sumatera - Hajjah, Siti; Batubara, Abdul Karim; Purwaningtyas, Franindya (Pena Cendekia Insani, 2022)
This study discusses the Strategy for Child Service Development at the Library of the Bank Indonesia Representative Office, North Sumatra Province. The purpose of this research is to see how the child development strategy is in the Library of the Bank Indonesia Representative Office, North Sumatra Province. This research method uses a qualitative descriptive approach. By using interview, observation and documentation techniques. The information in this study is librarians at the Library of the Bank Indonesia Representative Office in North Sumatra Province who have been selected by researchers in accordance with the criteria for research subjects.The results showed that the children's service development strategy carried out by librarians at the Library of Bank Indonesia Representative Office, North Sumatra Province, was carried out using promotion and socialization methods. Where the promotion is carried out using brochures and social media, namely Instagram. Meanwhile, the socialization was carried out by utilizing various competition activities organized by librarians and visiting schools to inform that the library of the Bank Indonesia Representative Office in North Sumatra Province provides a special service for children called the Kids Corner. The strategy for developing children's services aims to attract children's interest and attention to the Library of the Bank Indonesia Representative Office, North Sumatra Province.